DEVELOPMENT OF A WEB-BASED SCHOOL ADMINISTRATIVE PAYMENT APPLICATION USING PHP AND MYSQL: A CASE STUDY AT MTS AL KAROMAH - Jakiatul Himah, Siti; Haryono, Wasis; Ariestiandi, Deny; Septiani, Anny (LPPM AMIK CBI Sukabumi, 2025)
This study aims to analyze the current system for managing school administrative payment data implemented at MTs Al Karomah. In addition, this is research also seeks to identify the strengths and weaknesses of the existing system in order to uncover the problems that occur during the payment management process (Sugiyono, 2019). Based on the results of the analysis, the proposed solution is to design and develop a web based school administrative payment application using PHP and MySQL technologies tailored to the needs of the institution. The application is designed to simplify processes such as payment receipt, data storage, and administrative recording in a more accurate and structured manner (Rizal & Prasetyo, 2020). With the implementation of this system, it is expected that MTs Al Karomah will be able to improve the efficiency and effectiveness of school financial administration management. The application also enables administrative staff to generate financial reports quickly and in real-time, thereby enhancing transparency and accountability (Kusrini & Hermawan, 2018). Furthermore, the system is equipped with data security features and user access controls to protect sensitive information. The development of this information system employs relevant information technology approaches to support improved administrative management in the future (Jogiyanto, 2019).